The Analysis of the Levels of Turkish Candidate Teachers' Having the Values in the European Values Education Program - Hotaman, Davut (ELSEVIER SCIENCE BV, 2014)
The aim and problem of this study is to analyze the levels of Turkish candidate teachers' having the 12 values stated in the European Values Education Program in terms of some certain personal variables. In this descriptive study, a descriptive survey model was used. For this purpose, 443 Turkish candidate teachers were surveyed using a five point Likert-type Values Education Scale which encompasses the 12 values stated in the European Values Education Program and a Personal Information Form The data driven were analyzed using SPSS. T-test was used for two variables, ANOVA was used for multiple variables, and Tukey HSD test was used for the source of differences. Significant differences were determined among candidate teachers according to Gender, The Region of Primary Education, Number of Siblings, The Type of the Undergraduate Program, Social and Cultural Life Habits and The Type of the High School Education. As candidate teachers should improve themselves in the area of values education during the accession of Turkey to the European Union, Turkish candidate teachers should be involved in this program executed in Europe. (C) 2013 The Authors. Published by Elsevier Ltd. Selection and/or peer-review under responsibility of Academic World Education and Research Center.
Keywords: Value; Values Education; Candidate Teachers; Education & Educational Research